2004
DOI: 10.1109/joe.2004.840839
|View full text |Cite
|
Sign up to set email alerts
|

Internal Solitons in the Northeastern South China Sea Part I: Sources and Deep Water Propagation

Abstract: Abstract-A moored array of current, temperature, conductivity, and pressure sensors was deployed across the Chinese continental shelf and slope in support of the Asian Seas International Acoustics Experiment. The goal of the observations was to quantify the water column variability in order to understand the along-and across-shore low-frequency acoustic propagation in shallow water. The moorings were deployed from April 21-May 19, 2001 and sampled at 1-5 min intervals to capture the full range of temporal vari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

23
328
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 340 publications
(351 citation statements)
references
References 47 publications
23
328
0
Order By: Relevance
“…Over a decade of studies [8][9][10][11] have targeted the South China Sea, where the oceans' most powerful internal waves are generated in the Luzon Strait and steepen dramatically as they propagate west. Confusion has persisted regarding their generation mechanism, variability and energy budget, however, due to the lack of in-situ data from the Luzon Strait, where extreme flow conditions make measurements challenging.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Over a decade of studies [8][9][10][11] have targeted the South China Sea, where the oceans' most powerful internal waves are generated in the Luzon Strait and steepen dramatically as they propagate west. Confusion has persisted regarding their generation mechanism, variability and energy budget, however, due to the lack of in-situ data from the Luzon Strait, where extreme flow conditions make measurements challenging.…”
mentioning
confidence: 99%
“…When they shoal onto the continental slope to the west, the downward displacement of the ocean's layers associated with these solitary waves can exceed 250 m in 5 minutes 8 . On such a scale, these waves pose hazards for underwater navigation and offshore drilling 4 , and supply nutrients from the deep ocean that nourish coral reefs 1 and pilot whale populations that forage in their wakes 13 .…”
mentioning
confidence: 99%
“…Large ISWs are observed daily and their generation is due to the diurnal K 1 tide in the Luzon Strait that connects the SCS to the Western Pacific [Ramp et al, 2004;Klymak et al, 2006]. The induced flow dominates the upper ocean and hence an ISW can be observed by satellite as dark and light bands.…”
Section: Studies On the Source Of Internal Solitary Wave In The Southmentioning
confidence: 99%
“…It is well known that the barotropic tides in the SCS are dominated by diurnal constituents (Fang, Kwok, Yu, & Zhu, 1999;Yanagi & Takao, 1998). However, baroclinic tides are prominent in the semi-diurnal band of the NSCS (Du, Tseng, & Yan, 2008;Liao et al, 2010;Ramp et al, 2004;Zhao et al, 2004). Lien, Tang, Chang, and D'Asaro (2005) suggested that the strong internal tides generated in LS propagate into the SCS as a narrow tidal beam and produce nonlinear internal waves through interactions with islands and the continental slope.…”
Section: Introductionmentioning
confidence: 99%